“Regretting your brand-self?” The moderating role of consumer-brand identification on consumer responses to purchase regret - Davvetas, Vasileios; Diamantopoulos, Adamantios (Journal of business research, 2017)
Extending the study of consumer-brand relationships in the post-purchase stages of consumer decision making and in situations involving unfavorable comparisons with foregone brands, this research investigates the role of consumer-brand identification on consumer responses to purchase regret. Drawing on regret theory and consumer-brand relationship literature, the authors argue that consumer-brand identification immunizes the brand from the negative consequences of purchase regret through the amplification of consumers' cognitive regret regulation and the attenuation of consumers' behavioral regret coping. An empirical study using scenario manipulation of regret for participants' favorite brands provides support to the protective role of consumer-brand identification. The results indicate that consumer-brand identification attenuates the negative effects of regret on satisfaction and behavioral intentions and strengthens the positive impact of satisfaction on brand repurchase/recommendation intent. The findings enrich regret and consumer-brand relationship theories and provide managerial insights for effective branding strategy development under conditions of intense competitive pressure.